Text: "Perayaan gerakan pro demokrasi dan HAM atas penghargaan Mag Say Say Award kepada Dita Indah Sari"
Text: "Perayaan gerakan pro demokrasi dan HAM atas penghargaan Mag Say Say Award kepada Dita Indah Sari".